A comparative study of the attitudes of Urban, Suburban and Rural Police Officers in New Jersey regarding the use of force - Barrett, Kevin J. (Crime, law and social change, 2009)
This article examines the attitudes of sample populations of urban, suburban and rural police officers in New Jersey in regard to a hypothetical use of force scenario. The aim of the study is to identify similarities and differences in the perceptions of officers who are faced with the same type of hypothetical situations but who are exposed to different training, procedural and environmental factors. Police officers in the United States receive different types of training in each state that might influence their attitudes towards the use of force. A pilot study was conducted comparing two urban police departments from two different states and showed some differences in the attitudes of the surveyed officers. To further explore these differences, a more refined look at three police departments in one state (New Jersey) was conducted as part of a doctoral dissertation of the lead author. Research questions are aimed at identifying the differences in the frameworks for the justification of force based on a host of variables. The research questions stipulated that there will be some significant differences in attitudes towards the use of force by the officers, based on physical location of the communities they police. The findings of the study identified additional factors that might influence the officers’ attitudes. Twelve focus groups, four at each of the sites, were analyzed and it appears that there may be a geographic and demographic influence on how the officers respond to the scenario.